THE COURT TRADITION OF ACARÍ HUARATO AND ITS REACTIONS WITH NASCA - Valdez, Lidio M. (2000)
On the basis of recent archaeological research, the author discusses the Early Intermediare Period occupation of Acad valley. The study is oriented to verify whether occurred a nasca conquest and occupation of Acarí. The postery study indicates the presence of a local tradicion, at which context Early Nasca ceramics were introduced